The Relationship Between peer Conformity and Student's Career Planning - Abdul Hanan; Yarmis Syukur (International Journal of Applied Counseling and Social Sciences, 2025)
High school students are in the adolescent phase of development. During this phase, one of the most important developmental tasks is planning for their future careers. However, the career planning process is often influenced by various environmental factors, one of which is peer conformity. This study aims to examine the relationship between peer conformity and students' career planning. The research employed a quantitative correlational approach, with a sample of 238 students drawn from a total population of 654 students in Grade X Phase E and Grade XI Phase F at SMA Negeri 13 Padang, selected using stratified random sampling. Data were collected using Likert-scale instruments to measure peer conformity and career planning, both of which were developed and tested for validity and reliability. The data were analyzed using descriptive statistics and Pearson correlation with SPSS 25.0. The results revealed that both peer conformity and students' career planning were categorized as high. A strong and significant positive relationship was found between peer conformity and career planning (r = 0.678; p < 0.01). The implication is that school guidance and counseling services can utilize peer group interactions as a strategy to enhance the effectiveness of students' career planning.